KUALITAS PELAYANAN DAN KEPUASAN MAHASISWA SEBAGAI ANTESEDEN VALENSI WORD OF MOUTH PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH MALANG - H. B. Ardianto; Nazaruddin Malik; Eko Handayanto (Universitas muhammadiyah malang, 2012)
H. B. Ardianto*)Nazaruddin Malik **) dan Eko Handayanto **)Magister Manajemen Universitas Muhammadiyah MalangE-mail: Hbardianto@yahoo.co.idABSTRACTA research to examined the effect service quality toward student satisfaction, effect of service qualitytoward word of mouth valence, effect of student satisfaction toward word of mouth valence of studentUniversity of Muhammadiyah Malang. The treatment were used questionnaire, each statement onquestionnaire used to know respondent respon very disagree until very agree. Based on answerquestionnaire result collected 105 responden, data were analysis technique of Structural EquationModel (SEM). The result show that service quality has a positive influence and significant towardstudent satisfaction, service quality has a positive influence but not significant toward word of mouthvalence, student satisfaction has a positive influence and significant toward word of mouth valence.Data result show that service quality has an indirect positive influence toward word of mouth valencethrough student satisfaction. Student satisfaction has a direct positive influence and significant towardword of mouth valence on private university.Key words: service quality, satisfaction, word of mouth valence